TMS 320C31-based narrow-band noise rejection Kalman filter implementation - Dejhan, K.; Yimmun, S.; Trirat, A.; Cheevasuvit, F. (My University, 2002)
This paper proposes a design and development of narrow frequency band filter based on Kalman algorithm by using TMS 320C31 as processor. The center frequency of this filter is between 10 Hz to 1.5 kHz by changing the coefficient of sinusoidal model in normal form realization and the results have been carried out. It is used to reject the narrow-band noises.
Keywords: Kalman filter; TMS 320XXX